The Dialectics of Praxis and Theoria in African Philosophy : an Essay on Cultural Hermeneutics. (Langaa RPCIG, 2011)
This book is a clarion call for African renaissance informed by African spirituality. It develops the vision that Africans can be the same in the process of change. Africans have to coincide with their ways of perceiving values, and to retrieve their identity wiped out by regrettable historical events. Even in this involvement of revalorisation of their stifled ways, Africans have to be aware of the fact that history has evolved and new human environments are taking place. Any attempt to recover African personality involves a triple necessity. First, to remember the past, second, to analyse critically what Africans have inherited from their past, and lastly, to project new ways and means for a genuine renaissance, free from alienation and exploitation. Bin-Kapela sees in Cultural hermeneutics an appropriate philosophical method to achieve this end of recognising and projecting African spirituality as a universal value.